2017
DOI: 10.18006/2017.5(1).001.006
|View full text |Cite
|
Sign up to set email alerts
|

Haemato-biochemical profile and milk leukocyte count in subclinical and clinical mastitis affected crossbred cattle

Abstract: The study was conducted to determine the effect of subclinical mastitis (SCM) and clinical mastitis (CM) on haemato-biochemical parameters and milk leukocyte count of crossbred cattle. Milk and blood samples were collected from 20 healthy, 223 SCM and 47 CM affected animals from Kolar and Chikkaballapur districts of Karnataka state, India. The SCM were diagnosed by California Mastitis Test (CMT) and electrical conductivity (EC) of milk. Blood and milk of mastitis infected crossbred cattle were analyzed for hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Statistical analysis indicated a significant (p<0.01) decrease in Hb, PCV, and TEC, while TLC increased significantly (p<0.01) in subclinical affected cows. Previous studies support that the higher leukocyte count along with anemia in mastitic cows was reported (Sarvesha et al, 2017). They also emphasizing that the potential use of haemato biochemical parameters and milk leukocyte count as indicators for the physiological or pathological state of the animal, specifically mastitis.…”
Section: Resultsmentioning
confidence: 57%
“…Statistical analysis indicated a significant (p<0.01) decrease in Hb, PCV, and TEC, while TLC increased significantly (p<0.01) in subclinical affected cows. Previous studies support that the higher leukocyte count along with anemia in mastitic cows was reported (Sarvesha et al, 2017). They also emphasizing that the potential use of haemato biochemical parameters and milk leukocyte count as indicators for the physiological or pathological state of the animal, specifically mastitis.…”
Section: Resultsmentioning
confidence: 57%
“…The current study reveled significant decrease in PCV, RBCc and Hb with increase ratio in WBCc in infected cows compared to control cows. Differential cell count showed Neutrophilia and slightly increase in Monocyte ratio [15] observed a significant increase in WBC and decrease Hb, RBCc, PCV ratio which are due to in alternative animals. However higher neutrophila ratio reveled along with anemia and lymphopenia was earlier reported in mastitic cattle's.Further the current study find out more alteration hematological and biochemical profiles can be considered as monitor for state of animals.…”
Section: Resultsmentioning
confidence: 82%
“…Increase in leukocyte and neutrophil count in cattle with mastitis [Krishnappa,2016;Singh,2014;Tripathy,2018;Atroshi,1996;Sarvesha,2017;Sadek,2017;Alhussien,2015]. Contrary to this finding by several researchers, a research conducted to know alteration in blood parameters based on causative agent shows decrease in white blood cells in gram negative mastitis (Smith,2001).Decrease in lymphocytes and macrophages in the infected cattle (Krishnappa,2016;Alhussien,2015;Sarvesha, 2017).…”
Section: Alterations In White Blood Cellsmentioning
confidence: 97%
“…About 21% of the milk yield and is reduced and 25% of butter fat is reduced in the affected cattle (Chakrabarti, 2014).Older animals and a higher lactation has a higher chance of infection (Radiostits, 2010).Various changes are found in blood parameters in cattle affected with mastitis. Change in hematobiochemical parameters play an important role to rule out physiological and pathological state of mastitis in affected animal (Sarvesha, 2017). This short communication aims to understand the changes and findings occurred during the disease conditions conducted by different researchers.…”
Section: Introductionmentioning
confidence: 99%